1996
DOI: 10.1103/physrevlett.77.4824
|View full text |Cite
|
Sign up to set email alerts
|

Charge Redistribution in Pd-Ag Alloys from a Local Perspective

Abstract: Using Pd and Ag L 3,2 -edge x-ray-absorption near edge structures (XANES) and x-ray photoemission spectroscopy, we have investigated the charge distribution in a series of Pd-Ag alloys (Pd 3 Ag, PdAg, and PdAg 3 ) from a local perspective. It is found that, relative to the pure element, both Pd and Ag gain d and lose non-d (s and p) charge upon alloying. The results are discussed in terms of band filling, rehybridization, electronegativity, and electroneutrality considerations. The possibility of using the L 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 12 publications
10
92
1
Order By: Relevance
“…Although this argument works well for compounds of non-transition elements, it is generally not valid for metallic alloys with full or nearly full d-bands. 40,41 In particular, it is observed that the 3d core level shifts of both Ag and Pd have the same sign. 42 Abrikosov et al have explained this behaviour in terms of intra-atomic charge re-distribution due to valence electron hybridization.…”
Section: Methodsmentioning
confidence: 82%
“…Although this argument works well for compounds of non-transition elements, it is generally not valid for metallic alloys with full or nearly full d-bands. 40,41 In particular, it is observed that the 3d core level shifts of both Ag and Pd have the same sign. 42 Abrikosov et al have explained this behaviour in terms of intra-atomic charge re-distribution due to valence electron hybridization.…”
Section: Methodsmentioning
confidence: 82%
“…The pre-edges and backgrounds were subtracted and the measurements were normalised at 50 eV beyond the edge. Some saturation was visible when comparing the results to the literature [8]. A numerical compensation was determined for Pd and Pd/Ag under vacuum, which was also applied to the hydrogen measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The value of m B was determined by steering the relative intensity of the white-line (compared to the baseline) to the values for pure Pd respectively Pd 0.8 Ag 0.2 as determined by Coulthard and Sham,16 while the baseline was kept at 1 with the aid of a normalization factor. The energy scales of the spectra were calibrated on the point of inflection of the Pd L 3 edge, 3173.3 eV, 22 of the pure Pd sample in vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…Some saturation effects due to self-absorption were visible when comparing our fluorescence results to transmission results from Coulthard and Sham. 16 A numerical correction was determined based on the vacuum measurements of the two samples and applied to the hydrogen measurements. The correction was based on work by Schroeder; 21 for a 901 scattering angle the intensity of the fluorescence yield (I F ) is given as a function of the absorption cross section (m x ) and the background absorption (m B ):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation